Wayside School beneath the Cloud of Doom - Sachar, Louis, 1954-; Heitz, Tim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
"Follows the adventures and misadventures of students and staff as they cope with the effects of a large, gloomy cloud that has settled over Wayside School"--OCLC.
3-6
Keywords: Clouds -- Juvenile fiction; Schools -- Juvenile fiction; Clouds -- Fiction; Schools -- Fiction; Clouds -- Fiction; School stories; Humorous fiction